Substâncias húmicas de um latossolo vermelho-amarelo álico da região de Viçosa, Minas Gerais - Villani Longo , Jacqueline; Fernandes , Bairon; Alves Moreira, Maurílio; Resende , Mauro; Gomide Loures , Emílio (Revista Ceres, 2025)
This study was concerned with the humic substances of a Red-Yellow Latosol, located in the region of Viçosa, State of Minas Gerais.